ANALISIS KEUNGGULAN KOMPARATIF PENGEMBANGAN TERNAK KERBAU DI KABUPATEN PADANG LAWAS - Harahap, Salsabila; Hutasuhut, Ulina; Hafni, Syafrida (Jurnal Peternakan (Jurnal of Animal Science), 2024)
The development of buffalo livestock in Padang Lawas Regency has significant potential for regional economic growth. This study aims to analyze the comparative advantage of buffalo livestock development using the Location Quotient (LQ) method and identify supporting and inhibiting factors. The research was conducted in Padang Lawas Regency, North Sumatra Province, from February to March 2024. The study utilized secondary data from 2019 to 2023, analyzed using the Location Quotient (LQ) method and Growth Ratio Model (MRP). Results show that 11 out of 17 sub-districts in Padang Lawas Regency are classified as base areas for buffalo livestock (LQ 1), with Huristak sub-district having the highest LQ value (3.5867). The MRP analysis indicates positive growth in several sub-districts, particularly Barumun (RPs 5.237) and Ulu Barumun (RPs 0.907), despite a declining trend at the provincial level (RPr -0.440). Supporting factors include proactive government policies, availability of high-quality feed, and the use of modern technology. Inhibiting factors encompass inadequate infrastructure, limited financial resources for small-scale farmers, and animal health issues. This research provides valuable insights for policymakers and stakeholders in developing targeted strategies to enhance buffalo livestock production in Padang Lawas Regency.Keywords: Buffalo, Location Quotient, Growth Ratio Model, Comparative Advantage, Padang Lawas